Characteristics and outcomes of patients with cancer hospitalized with new onset acute heart failure - Giancarlo Marenzi; Daniela Cardinale; Nicola Cosentino; Filippo Trombara; Paolo Poggio; Olivia Leoni; Francesco Bortolan; Marta Resta; Claudia Lucci; Nicolò Capra; Alice Bonomi; Piergiuseppe Agostoni (ESC Heart Failure)
Abstract Aims Limited evidence exists regarding the outcomes of cancer patients hospitalized with new onset acute heart failure (AHF). We assessed the in‐hospital mortality and 1 year outcomes of cancer patients admitted for new onset AHF, taking into account both past and active cancer status as well as cancer site. Methods We examined administrative data of adult patients hospitalized with a first episode of AHF from 2003 to 2018 in Lombardy, Italy. Patients were categorized based on their cancer history. The primary endpoint was in‐hospital mortality with secondary endpoints including 1 year all‐cause mortality and 1 year re‐hospitalization for AHF. Results Among 283 144 patients AHF hospitalizations, 55 145 (19%) involved patients with a history of cancer (60% past cancer, 40% active cancer). Both in‐hospital and 1 year mortality rates were higher among cancer patients compared with those without (9.3% vs. 6.4% and 34.9% vs. 22.3%, respectively; P < 0.0001). After adjustment, cancer patients exhibited increased risk of in‐hospital mortality [odds ratio (OR) 1.40; 99% confidence interval (CI) 1.34–1.46] and 1 year mortality (HR 1.35; 99% CI 1.32–1.39), particularly among those with lung cancer. Patients with active and past cancer had a similar in‐hospital mortality risk (OR 0.99; 99% CI 0.91–1.07) while 1 year mortality risk was higher among those with active cancer (HR 1.26; 99% CI 1.21–1.31). Conclusions Cancer is a prevalent comorbidity in patients hospitalized with new onset AHF, and it is associated with a poorer prognosis. Mortality risk appears to vary based on cancer status and type.